Financial analysis of East Coast fever control strategies on beef production under farm conditions - Mukhebi, A.W.; Wathanga, J.; Perry, Brian D.; Irvin, A.D.; Morzaria, S.P. (1989)
Provides a financial analysis of East Coast fever control strategies on beef production under farm conditions. Assesses the effects of immunisation by the infection and treatment method, under different acricidal treatments, on the productivity of beef cattle in Kenya.